2018
DOI: 10.1080/13811118.2018.1515136
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Correlates of Self-Harm within Gay, Lesbian and Bisexual UK University Students

Abstract: This study explores the association between lesbian, gay or bisexual (LGB) status and self-harm in UK higher education students. There is currently limited data on this association, and the role psychological variables have in potentially explaining this link, in UK students. We examine whether LGB status is associated with self-harm (both non-suicidal self-injury [NSSI] and suicide attempts [SA]), and whether 4 psychological variables (depression, anxiety, belongingness, self-esteem) mediate this association.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 63 publications
4
33
0
1
Order By: Relevance
“…Self-esteem was positively associated with engagement in wellness behaviors and-aside from age-represented the strongest relationship among all predictors, which supports previous work showing that higher self-esteem is related to positive health behaviors [24], psychosocial health [31], and well-being in health [35]. Recent work by Taylor and colleagues [36] has also investigated self-esteem as it relates to self-injury (including self-mutilation, attempted suicide, and substance abuse behaviors) among LGBT individuals and found that self-esteem negatively predicted this relationship above and beyond anxiety and depressive symptoms. The present study, in conjunction with previous work, suggests that feelings of self-worth among LGBT individuals may be a crucial factor in determining engagement in wellness and health promoting behaviors.…”
Section: Discussionsupporting
confidence: 80%
“…Self-esteem was positively associated with engagement in wellness behaviors and-aside from age-represented the strongest relationship among all predictors, which supports previous work showing that higher self-esteem is related to positive health behaviors [24], psychosocial health [31], and well-being in health [35]. Recent work by Taylor and colleagues [36] has also investigated self-esteem as it relates to self-injury (including self-mutilation, attempted suicide, and substance abuse behaviors) among LGBT individuals and found that self-esteem negatively predicted this relationship above and beyond anxiety and depressive symptoms. The present study, in conjunction with previous work, suggests that feelings of self-worth among LGBT individuals may be a crucial factor in determining engagement in wellness and health promoting behaviors.…”
Section: Discussionsupporting
confidence: 80%
“…Supportive evidence from a study of community‐dwelling older adults showed a negative association of self‐esteem with PB, TB, and suicidal ideation (Eades, Segal, & Coolidge, ). Additionally, self‐esteem and TB explained some of the elevated risk of suicide among lesbian, gay, or bisexual individuals and correlated with risk of self‐harm (Taylor et al, ). Low self‐esteem, depression, and trait anxiety predicted suicide probability among alcohol‐dependent subjects (Demirbas et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between PB and TB was significantly associated with suicidal ideation, whereas the interaction between PB, TB, and acquired capability for suicide was significantly associated with a greater number of prior suicide attempts (Chu et al, ). Nonetheless, while the IPTS may explain the transition from suicidal ideation to lethal suicide attempt, it does not explicitly account for factors that may influence the development of suicidality such as substance misuse, depression, self‐esteem, personality traits, and childhood abuse (Baertschi, Costanza, Canuto, & Weber, ; Roy, ; Silva, Ribeiro, & Joiner, ; Taylor, Dhingra, Dickson, & McDermott, ).…”
mentioning
confidence: 99%
“…This can be specific tools for considering suicide, for example, Beck Scale for Suicide Ideation;49 Motto’s Risk Estimator for Suicide;50 Positive and Negative Suicide Ideation;51 Columbia-Suicide Severity Rating Scale;52 or self-harm, for example, Self-Harm Inventory;53 Inventory of Statements about Self-injury;38 Self-Injurious Thoughts and Behaviour Interview Short Form 54. Also included will be self-harm or suicide items from general scales such as items 102–105 from the Mental Health History Form (Boudewyn and Liem, 1995; Mental Health History Form) or individual questions regarding self-harm or suicide had ever been considered or acted on55 and clinician reports.…”
Section: Methodsmentioning
confidence: 99%